A review on hot cathode ionisation gauges with focus on a suitable design for measurement accuracy and stability. (September 2020) - Jousten, Karl; Boineau, Frederic; Bundaleski, Nenad; Illgen, Claus; Setina, Janez; Teodoro, Orlando M.N.D.; Vicar, Martin; Wüest, Martin
Abstract: A literature review starting from 1950 is given on the design and geometry of ionisation gauge types with hot cathodes. Considerations on the material of the electrodes and of surface effects are included. The review focuses on the design issues for measurement accuracy, linearity, repeatability, reproducibility, and stability of sensitivity. Also, the attempts to reduce the lower measurement limit are reviewed to some extent. Highlights: Literature review on the design and geometry of ionisation gauges with hot cathodes. Considerations on material of the electrodes and of surface effects are included. Review focuses on issues for measurement accuracy and stability of sensitivity.